Incorporating risk input into the analysis of bank productivity: Application to the Taiwanese banking industry - Chen, Ku-Hsieh (Journal of Banking & Finance, 2012)
This study reappraises banks’ productivity by using 42 Taiwanese banks during 1999–2007 as observations. It introduces an input-oriented generalized metafrontier Malmquist productivity index (I-gMMPI), while considering the latent effect of risk-taking behavior in the analytic framework. We learn that public and private banks should face separate short-term technological frontiers, while the econometric model considering risk input can portray banks’ operating frontiers better. Moreover, neglecting the influence of risk input would bring about distortions of efficiency, technology and TFP dynamic estimations for banks; meanwhile, the degree of scale economies would also be overestimated. The paper concludes that neglecting the risk-taking essence in bank performance evaluation is equal to allowing banks to barter risk-bearing as the term for further output growth. Consequently, the potential cost is that banks may excessively aggrandize their scales of business, implying the possibility of another financial crisis.